Implementation of Metaverseting Based Pedagogy for the Transformation of Collaborative Learning Experiences in the Digital Education Ecosystem - Maulana Paramaditya Ananta; Dedi Gunawan Saputra (Institut Bahri Asyiq Galis Bangkalan, 2025)
The transformation of digital education has required pedagogical approaches capable of fostering meaningful and contextual collaborative learning experiences. The development of metaverse environments has created new opportunities to establish immersive learning spaces; however, their implementation has often remained technology-oriented and has not been supported by a systematic pedagogical framework. This study aimed to analyze the implementation of metaverseting-based pedagogy in transforming collaborative learning experiences within the digital education ecosystem. A qualitative approach with an interpretative case study design was employed. Data were collected through in-depth interviews, virtual participant observation, and document analysis, and were examined using thematic analysis. The findings indicated that metaverseting-based pedagogy reconstructed collaborative learning design, strengthened students’ social and cognitive presence, and enhanced engagement and knowledge co-creation within digital learning spaces. The results also revealed that the successful implementation of metaverseting was strongly influenced by the support of the digital education ecosystem, including institutional policies, infrastructure readiness, and digital pedagogical literacy. This study contributed to the development of a conceptual framework for metaverseting pedagogy and offered practical implications for educators and institutions in designing collaborative learning within immersive virtual environments.